The effect of rhythmic deep breathing on pain and anxiety in patients with burns - Anjana Rajhamsan Iyer; Suroshree Mitra; Rachana Dabadghav (Wolters Kluwer Medknow Publications, 2020)
Context: Patients with burns suffer from physical (pain) and psychosocial (anxiety) sequelae due to the burns wounds and mobilization activities. Deep breathing is a simple intervention to manage pain and anxiety in various conditions. Data concerning the effect of breathing on burns patients are limited. In order to add to this information, this study was undertaken on burns patients. Aims and Objectives: The aim was to study the effect of rhythmic deep breathing on pain and anxiety in patients with burns. Methods: This study followed an experimental, pretest-posttest design. A single group of twenty patients in the age group of 5-70 years who had suffered various types of burns to some or all parts of the body were recruited from a tertiary care center in Pune, India. With institutional approval and written consent, deep breathing technique was taught to the patients. Pretest and posttest scores of pain visual analog scale (VAS), anxiety (VAS), and anticipatory anxiety pain anxiety symptom scale were collected in the period from October 2019 to November 2019. Results: Significant change (P = 0.00) was observed in the mean pain, anxiety, and anticipatory anxiety scores over time. Conclusion: Rhythmic deep breathing can significantly help to decrease pain and anxiety in patients with burns.